Copper homeostasis and neurodegenerative diseases - Yuanyuan Wang; Daidi Li; Kaifei Xu; Guoqing Wang; Feng Zhang (Neural Regeneration Research)
Copper, one of the most prolific transition metals in the body, is required for normal brain physiological activity and allows various functions to work normally through its range of concentrations. Copper homeostasis is meticulously maintained through a complex network of copper-dependent proteins, including copper transporters (CTR1 and CTR2), the two copper ion transporters the Cu -transporting ATPase 1 (ATP7A) and Cu-transporting beta (ATP7B), and the three copper chaperones ATOX1, CCS, and COX17. Disruptions in copper homeostasis can lead to either the deficiency or accumulation of copper in brain tissue. Emerging evidence suggests that abnormal copper metabolism or copper binding to various proteins, including ceruloplasmin and metallothionein, is involved in the pathogenesis of neurodegenerative disorders. However, the exact mechanisms underlying these processes are not known. Copper is a potent oxidant that increases reactive oxygen species production and promotes oxidative stress. Elevated reactive oxygen species levels may further compromise mitochondrial integrity and cause mitochondrial dysfunction. Reactive oxygen species serve as key signaling molecules in copper-induced neuroinflammation, with elevated levels activating several critical inflammatory pathways. Additionally, copper can bind aberrantly to several neuronal proteins, including alpha-synuclein, tau, superoxide dismutase 1, and huntingtin, thereby inducing neurotoxicity and ultimately cell death. This study focuses on the latest literature evaluating the role of copper in neurodegenerative diseases, with a particular focus on copper-containing metalloenzymes and copper-binding proteins in the regulation of copper homeostasis and their involvement in neurodegenerative disease pathogenesis. By synthesizing the current findings on the functions of copper in oxidative stress, neuroinflammation, mitochondrial dysfunction, and protein misfolding, we aim to elucidate the mechanisms by which copper contributes to a wide range of hereditary and neuronal disorders, such as Wilson’s disease, Menkes’ disease, Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, Huntington’s disease, and multiple sclerosis. Potential clinically significant therapeutic targets, including superoxide dismutase 1, D-penicillamine, and 5,7-dichloro-2-[(dimethylamino)methyl]-8-hydroxyquinoline, along with their associated therapeutic agents, are further discussed. Ultimately, we collate evidence that copper homeostasis may function in the underlying etiology of several neurodegenerative diseases and offer novel insights into the potential prevention and treatment of these diseases based on copper homeostasis.